White noise [videorecording (DVD)] - Sax, Geoffrey; Keaton, Michael, 1951-; Unger, Deborah Kara; West, Chandra, 1970-; McNeice, Ian; Strange, Sarah; Seager, Chris; Foisy, Claude (Universal Studios Home Video, 2005)
A man who is shattered by the death of his wife is contacted by a man who claims to be receiving messages from her through 'white noise'. When he becomes convinced of the messages' validity, he tries to contact her on his own.